The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1016/0014-5793(92)81173-j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an ion channel‐forming motif in the primary structure of tetanus and botulinum neurotoxins

Abstract: Synthetic peptides with amino acid ~eqttences corresponding to predicted transmembran¢ segments of tet~tntts toxin were used as probes to identify a elmnnel-forming motif. A peptide denoted TeTx 1I. with sequence GVVLLLEYIPEITLPVIAALSIA, form.~ cation-selective channels when r~onztltuted in planar lipid bilaycrz. The .~ia~le channel conductance in 0.~ M NaCI or KCI is 28 + 3 ~tnd 24 ± 2 pS. respectively. In contrast, a peptide with sequence NFIGALETTGVVLLLEYIPEIT. denoted as TeTx I. or a peptide with the mine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 39 publications
(34 reference statements)
0
35
0
Order By: Relevance
“…Molecular modeling, energy minimization, and molecular dynamics simulations, were conducted on a Silicon Graphics IRIS 4D/210 GTXB workstation using the INSIGHT and DIS-COVER molecular modeling packages of Biosym (San Diego, California) (Oiki et al, 1990;Montal et al, 1990Montal et al, , 1992. Lowenergy arrangements of a-helices and four-helix bundles were calculated with semiempirical potential energy functions and optimization routines.…”
Section: Con Formational Energy Computationsmentioning
confidence: 99%
“…Molecular modeling, energy minimization, and molecular dynamics simulations, were conducted on a Silicon Graphics IRIS 4D/210 GTXB workstation using the INSIGHT and DIS-COVER molecular modeling packages of Biosym (San Diego, California) (Oiki et al, 1990;Montal et al, 1990Montal et al, , 1992. Lowenergy arrangements of a-helices and four-helix bundles were calculated with semiempirical potential energy functions and optimization routines.…”
Section: Con Formational Energy Computationsmentioning
confidence: 99%
“…After binding, the toxin is internalized into an endosome through receptor-mediated endocyctosis [17,18]. The amino-terminal half of the heavy chain (H N ) is believed to participate in the translocation mechanism of the light chain across the endosomal membrane [4,[19][20][21][22]. The low pH environment of the endosome may trigger a conformational change in the translocation domain, thus forming a channel for the light chain.…”
Section: Introductionmentioning
confidence: 99%
“…Native gel electrophoresis and chemical crosslinking experiments have shown that TeNT forms dimers and trimers in solution [26]. Previous cryoelectron microscopy [23] and ion conductance [24] studies have also shown that both botulinum toxin and TeNT can form tetrameric channels in neuronal membranes. However, higher order TetC oligomers, such as trimers or tetramers, were not observed in the ESI-MS data presented here, probably because of the mass range limitations of the Mariner mass spectrometer used.…”
Section: Tetc Dimerizationmentioning
confidence: 97%
“…Following its binding to gangliosides and a protein receptor, TeNT oligomerizes and is pulled into an endosome where it forms a channel or pore in the cell membrane through which it transfers its catalytic domain [22][23][24][25]. Native gel electrophoresis and chemical crosslinking experiments have shown that TeNT forms dimers and trimers in solution [26].…”
Section: Tetc Dimerizationmentioning
confidence: 99%